Effect Of Nigella sativa Cement Extract on Procalcitonin, TNF-α Level and Time to Clinical Stable in Pneumonia Patients - Lusiana Susilo Utami; Reviono Reviono; Suradi Suradi; Harsini Harsini; Jatu Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Background: Pneumonia is an infectious disease with highest morbidity and mortality in the world. The research objectives is to determine the effect of Nigella sativa cement extract in procalcitonin, TNF-α levels, and clinical improvement in pneumonia patients. Methods: This study is a clinical trial quasi experimental design with pre and post test approach in the treatment group and the comparison group. Samples were taken by consecutive sampling between April and May 2016 a total of 30 patients were divided into 2 groups:the treatment group and the comparison group. The treatment group was given additional therapy capsules Nigella sativa cement extract, the comparison group was given the standard therapy. Procalcitonin levels and TNF-α is checked when the patient was admitted and when clinical improvement is achieved. Results: Decreased levels of procalcitonin in the treatment group (8.969±13.591 ng/dl) and a comparison group (1.907±6293 ng/dl) was statistically significant (p= 0.014; 95 % CI= 0.222-1.770). Decreased levels of TNF-α was not significantly different between treatment groups (58.759(1.840-166.50) pg/dl) and a comparison group (57.485 (35.410-81.650) pg/dl), with p= 0.395. The achievement of clinical improvement in the treatment group 4.60±8.28 days and the comparison group 5.53 ±1.45 today, statistically no difference between the two groups. Conclusion: Capsule Nigella sativa cement extract provides benefit for declining levels of procalcitonin and accelerate achievement of clinically stable in pneumonia patients. (J Respir Indo. 2017; 37(4): 316-24)